(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study was conducted in the eastern plain of Rajasthan. Conventional farmers are still facing various constraints; hence the study entitled “Constraints Faced by the Inorganic farmers in the Eastern Plain of Rajasthan” was conducted in eleven villages